Defining and Verifying Durable Opacity: Correctness for Persistent Software Transactional Memory - Bila, Eleni; Doherty, Simon; Dongol, Brijesh; Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Formal Techniques for Distributed Objects, Components, and Systems - 40th IFIP WG 6.1 International Conference, FORTE 2020, Held as Part of the 15th International Federated Conference on Distributed Computing Techniques, DisCoTec 2020, Valletta, Malta, June 15-19, 2020, Proceedings)

Consistency Analysis of AUTOSAR Timing Requirements - Beringer, Steffen; Wehrheim, Heike (Proceedings of the 15th International Conference on Software Technologies, ICSOFT 2020, Lieusaint, Paris, France, July 7-9, 2020)

Verification Artifacts in Cooperative Verification: Survey and Unifying Component Framework - Beyer, Dirk; Wehrheim, Heike (Leveraging Applications of Formal Methods, Verification and Validation: Verification Principles - 9th International Symposium on Leveraging Applications of Formal Methods, ISoLA 2020, Rhodes, Greece, October 20-30, 2020, Proceedings, Part I)

Fundamental Approaches to Software Engineering - 23rd International Conference, FASE 2020, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2020, Dublin, Ireland, April 25-30, 2020, Proceedings

Tests and Proofs - 14th International Conference, TAP@STAF 2020, Bergen, Norway, June 22-23, 2020, Proceedings [postponed]

Testing Monotonicity of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (CoRR)

Mapping postprandial responses sets the scene for targeted dietary advice - Brand-Miller, Jennie; Buyken, Anette (Nature Medicine)

The relationship between differences in students’ computer and information literacy and response times: an analysis of IEA-ICILS data - Heldt, Melanie; Massek, Corinna; Drossel, Kerstin; Eickelmann, Birgit (Large-scale Assessments in Education)
Abstract Background Due to the increasing use of information and communication technology, computer-related skills are important for all students in order to participate in the digital age (Fraillon, J., Ainley, J., Schulz, W., Friedman, T. & Duckworth, D. (2019). Preparing for life in a digital world: IEA International Computer and Information Literacy Study 2018 International Report. Amsterdam: International Association for the Evaluation of Educational Achievement (IEA). Retrieved from https://www.iea.nl/sites/default/files/2019-11/ICILS%202019%20Digital%20final%2004112019.pdf ). Educational systems play a key role in the mediation of these skills (Eickelmann. Second Handbook of Information Technology in Primary and Secondary Education. Cham: Springer, 2018). However, previous studies have shown differences in students’ computer and information literacy (CIL). Although various approaches have been used to explain these differences, process data, such as response times, have never been taken into consideration. Based on data from the IEA-study ICILS 2013 of the Czech Republic, Denmark and Germany, this secondary analysis examines to what extent response times can be used as an explanatory approach for differences in CIL also within different groups of students according to student background characteristics (gender, socioeconomic background and immigrant background). Methods First, two processing profiles using a latent profile analysis (Oberski, D. (2016). Mixture Models: Latent Profile and Latent Class Analysis. In J. Robertson & M. Kaptein (Eds.), Modern Statistical Methods for HCI (pp. 275–287). Switzerland: Springer. 10.1007/978-3-319-26633-6 ) based on response times are determined—a fast and a slow processing profile. To detect how these profiles are related to students’ CIL, also in conjunction with students’ background characteristics (socioeconomic and immigrant background), descriptive statistics are used. Results The results show that in the Czech Republic and Germany, students belonging to the fast processing profile have on average significantly higher CIL than students allocated to the slow processing profile. In Denmark, there are no significant differences. Concerning the student background characteristics in the Czech Republic, there are significant negative time-on-task effects for all groups except for students with an immigrant background and students with a high parental occupational status. There are no significant differences in Denmark. For Germany, a significant negative time-on-task effect can be found among girls. However, the other examined indicators for Germany are ambiguous. Conclusions The results show that process data can be used to explain differences in students’ CIL: In the Czech Republic and Germany, there is a correlation between response times and CIL (significant negative time-on-task effect). Further analysis should also consider other aspects of CIL (e.g. reading literacy). What becomes clear, however, is that when interpreting and explaining differences in competence, data should also be included that relates to the completion process during testing.

Goal Achievement, Subsequent User Effort and the Moderating Role of Goal Difficulty - Gutt, Dominik; von Rechenberg, Tobias; Kundisch, Dennis (Journal of Business Research)

Enhancing social cohesion in PE classes within an intercultural learning program: results of a quasi-experimental intervention study - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Physical Education and Sport Pedagogy)

"Solange dieser Mann gut Deutsch sprechen kann, ist auch kein Problem...": Evaluative Reaktionen auf einen L2-Akzent aus Sicht von Sprecher*innen - Müller, Mareike; Settinieri, Julia (Fremdsprachen Lehren und Lernen)
This article investigates learners’ accounts of and reactions to interlocutors’ evaluations of their L2 pronunciation. Previous studies demonstrate both the pervasiveness of social evaluation processes in native and non-native speaker interactions and the impact of learners’ beliefs about pronunciation on their learning and communicative behavior. Adding to these strands of research, this project sheds light on how learners perceive evaluative reactions to their accents by native speakers and the relationship between such evaluations and learners’ reported evaluative, emotional and behavioral responses. The study draws on 8 international students at a German university. The data were collected in semi-structured interviews and analyzed within the framework of qualitative content analysis. The results give insight into conditions and strategies that may support learners in establishing constructive interpretations of the effects of their accents on their social acceptance.

Systematik zur Digitalisierung von Produktprogrammen - Echterfeld, Julian

Systematik zur integrativen Entwicklung von mechatronischen Produkten und deren Prüfmittel - Lukei, Meinolf

Die Anbahnung einer forschenden Grundhaltung im Praxissemester – eine empirische Analyse von Bedingungen und Entwicklungsverläufen - Homt, Martina

Above 60 GHz Bandwidth 10 GS/s Sampling Rate Track-and-Hold Amplifier in 130 nm SiGe BiCMOS Technology - Wu, Liang; Weizel, Maxim; Scheytt, Christoph (2020 IEEE International Symposium on Circuits and Systems (ISCAS))
This paper presents a broadband track-and-hold amplifier (THA) based on switched-emitter-follower (SEF) topology. The THA exhibits both large- and small-signal bandwidth exeeding 60 GHz. It achieves an effective number of bits (ENOB) of 7 bit at 34 GHz input frequency and an ENOB of >5 bit over the whole input frequency bandwidth at sampling rate of 10 GS/s. Much higher sampling rates are possible but lead to somewhat worse performance. The chip was fabricated in a 130 nm SiGe BiCMOS technology from IHP (SG13G2). It draws 78 mA from a -4.8 V supply voltage, dissipating 375 mW.

Sensitivity Analysis of a Low-Power Wake-Up Receiver Using an RF Barker Code SAW Correlator and a Baseband Narrowband Correlator - Abughannam, Saed; Scheytt, Christoph (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC 2020))
In this paper we propose a novel low-power receiver architecture which uses a direct-detection receiver in combination with a 2.44 GHz 13 bit Barker Code SAW correlator for improvement of co-channel interference. Furthermore, to improve receiver sensitivity, a narrowband baseband correlator which uses pulse position modulation (PPM) is proposed. The receiver can be used as a Wake-up Receiver (WuRx) in Wireless Sensor Networks (WSN) to minimize the power dissipation and provide asynchronous and on-demand data communication. We present a rigorous analysis of the receiver. It shows that the RF front-end (SAW correlator and envelope detector) alone suffers from poor sensitivity due to the high baseband bandwidth and the absence of an RF low noise amplifier. However, by adding the narrowband correlator with an innovative Pulse Position Modulation (PPM) scheme, the overall sensitivity of the receiver reaches -63.1 dB with an improvement of 17.7 dB due to the use of the narrowband correlator that reduces the baseband bandwidth from 50 to 0.84 MHz. By scaling the narrowband correlator bandwidth further down, the receiver sensitivity can be further improved.

A Scalable Platform for QEMU Based Fault Effect Analysis for RISC-V Hardware Architectures - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2020 - Methods and Description Languages for Modelling and Verification of Circuits and Systems; GMM/ITG/GI-Workshop)
Fault effect simulation is a well-established technique for the qualification of robust embedded software and hardware as required by different safety standards. Our article introduces a Virtual Prototype based approach for the fault analysis and fast simulation of a set of automatically generated and target compiled software programs. The approach scales to different RISC-V ISA standard subset configurations and is based on an instruction and hardware register coverage for automatic fault injections of permanent and transient bitflips. The analysis of each software binary evaluates its opcode type and register access coverage including the addressed memory space. Based on this information dedicated sets of fault injected hardware models, i.e., mutants, are generated. The simulation of all mutants conducted with the different binaries finally identifies the cases with a normal termination though executed on a faulty hardware model. They are identified as a subject for further investigations and improvements by the implementation of additional hardware or software safety countermeasures. Our final evaluation results with automatic C code generation, compilation, analysis, and simulation show that QEMU provides an adequate efficient platform, which also scales to more complex scenarios.

Analysis, Design and Implementation of a Fully Integrated Analog Front-End for Microwave RFIDs at 5.8 GHz to be Used with Compact MIMO Readers - Haddadian, Sanaz; Scheytt, Christoph (IEEE Journal of Radio Frequency Identification)
In this paper we present the system and circuit level analysis and feasibility study of applying microwave Radio Frequency Identification (RFID) systems with multipleinput multiple-output (MIMO) reader technology for tracking machining tools in multipath fading conditions of production environments. In the proposed system the MIMO reader interrogates single-antenna tags, and a high RFID frequency of 5.8 GHz is chosen to reduce the size of the reader's antenna array. According to the requirements dictated by the performed system analysis at 5.8 GHz, a low power fully integrated analog frontend (AFE) is designed and fabricated in a standard 65-nm CMOS technology for low power passive transponders. Performance of the Differential Drive Rectifier (DDR) topology as the core of the energy harvesting unit is investigated in detail. A multi-stage DDR power scavenging unit is dimensioned to provide a 1.2 V rectified voltage for 20-30 kQ load range, with a high power conversion efficiency (PCE) for high frequency and low input power level signals. The rectified voltage is then converted to a 1 V regulated voltage for the AFE and the baseband processor with 30 to 50 μW of estimated power consumption. Transistors with standard threshold voltage (VT) have been used for implementation. Measurements of the fabricated multi-stage configuration of the circuit show a maximum PCE of 68.8% at -12.46 dBm, and an input quality factor (Q-factor) of approximately 10. Amplitude-shift keying (ASK) demodulator and backscattering modulator with 80% modulation index, operating according to EPC-C1G2 protocol are applied for data transfer. The AFE consumes less than 1 μW in the reading mode. The AFE tag chip is 0.55 × 0.58 mm 2 .

Design and Fabrication of Barker Coded Surface Acoustic Wave (SAW) Correlator at 2.45 GHz for Low-Power Wake-up Receivers - Ballandras, Sylvain; Abughannam, Saed; Courjon, Emilie; Scheytt, Christoph (GeMiC 2020 - German Microwave Conference)
Low-power receivers use direct-detection receiver architecture for its design simplicity and its low power dissipation. However, the direct-detection based receivers suffer from co-channel interference which significantly degrades the communication reliability. Co-channel interference robustness can be improved by using a BPSK Barker code modulated Surface Acoustic Wave (SAW) correlator as a prior stage to the RF direct detection circuit. This paper reports in details the design, fabrication and measurements of a 2.45 GHz SAW correlator with 13 bits length Barker code. The device is fabricated on Lithium Niobate LiNbO3 substrate and it is composed of an input non-coded Inter Digital Transducers (IDT), a Piezoelectric substrate and an output coded IDT. The device wavelength λ is set to 1.6 μm, considering a phase velocity of the wave equal to 3970 m.s-1. Several configurations of the device were designed and fabricated, particularly varying the aperture and the non-coded IDT length to find out the optimal device configuration. All devices were found to operate with Insertion Loss (IL) ranging from 12 to 15 dB at 2.45 GHz with a tip probing measurement setup, while a packaged sample has an IL of 12.45 dB at 2.44 GHz mounted on a PCB with external 50 Ω LC matching network. Additionally, time-domain measurement for the packaged device shows that the output has a correlation peak with a peak-to-side-lobe (PSL) ratio of 4:1 for a -0.5 dBm input BPSK Barker code signal.

Ein interdisziplinärer und akutmedizinischer Ansatz zur frühestmöglichen Intervention bei Patienten mit Diabetischem Fußsyndrom - Schraeder, Dirk Theodor; Schafran, Tommy; Geisen, Bärbel; Rubbert, Lisa (Orthopädie Technik)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Der richtige Dreh für Simulationen - Schöppner, Volker; Austermeier, Laura; Dietl, Kilian (Blasformen & Extrusionswerkzeuge)
Keywords: Compoundieren; Doppenschneckenextruder; Energieeintrag

SKZ simuliert Doppelschnecke - Schöppner, Volker; Austermeier, Laura; Dietl, Kilian (K Zeitung)
Keywords: Compoundieren; Doppenschneckenextruder; Energieeintrag

DSPG: Decentralized Simultaneous Perturbations Gradient Descent Scheme - Ramaswamy, Arunselvan (2020 28th Euromicro International Conference on Parallel, Distributed and Network-Based Processing (PDP))

Constrained Multi-Agent Optimization with Unbounded Information Delay - Heid, Stefan Helmut; Ramaswamy, Arunselvan; Hüllermeier, Eyke (Proceedings-30. Workshop Computational Intelligence: Berlin, 26.-27. November 2020)

Asynchronous stochastic approximations with asymptotically biased errors and deep multi-agent learning - Ramaswamy, Arunselvan; Bhatnagar, Shalabh; Quevedo, Daniel E (IEEE Transactions on Automatic Control)

Interlaboratory study on rheological properties of cement pastes and reference substances: comparability of measurements performed with different rheometers and measurement geometries - Haist, Michael; Link, Julian; Nicia, David; Leinitz, Sarah; Baumert, Christian; von Bronk, Tabea; Cotardo, Dario; Eslami Pirharati, Mahmoud; Fataei, Shirin; Garrecht, Harald; Gehlen, Christoph; Hauschildt, Inga; et al. (Materials and Structures)
Abstract This paper presents the results of an interlaboratory study of the rheological properties of cement paste and ultrasound gel as reference substance. The goal was to quantify the comparability and reproducibility of measurements of the Bingham parameters yield stress and plastic viscosity when measured on one specific paste composition and one particular ultrasound gel in different laboratories using different rheometers and measurement geometries. The procedures for both in preparing the cement paste and carrying out the rheological measurements on cement paste and ultrasound gel were carefully defined for all of the study’s participants. Different conversion schemes for comparing the results obtained with the different measurement setups are presented here and critically discussed. The procedure proposed in this paper ensured a reasonable comparability of the results with a coefficient of variation for the yield stress of 27% and for the plastic viscosity of 24%, despite the individual measurement series’ having been performed in different labs with different rheometers and measurement geometries.

Stabilization of polyacrylonitrile nanofiber mats obtained by needleless electrospinning using dimethyl sulfoxide as solvent - Moritzer, Elmar; Wortmann, M.; Sabantina, L.; Klocker, M.; Mirasol, JR (JOURNAL OF INDUSTRIAL TEXTILES)

2K-Haftverbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Lochbaum, Ella (Plastverarbeiter)

Additive Manufactured Heat Pipe Injection Mould Element - Moritzer, Elmar; Kartelmeyer, Stephan; Hüttemann, Vincent (Direct Digital Manufacturing Conference 2020)

Additiveteile Direktverschrauben - Moritzer, Elmar; Hillemeyer, Johannes (6. Fachkonferenz 3D-Druck in der Automobielindustrie)

ANALYSIS OF THE ADVANTAGEOUS PROCESS AND MIXING BEHAVIOUR OF WAVE-DISPERSION SCREWS IN SINGLE SCREW EXTRUSION - Schöppner, Volker; Dörner, M.; Marschik, C.

Ansatz zur sicheren Direktverschraubung additiv gefertigter Einschraubtuben - Moritzer, Elmar; Hillemeyer, Johannes (10. Gemeinschaftskolloquium)

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part B. (Superimposed Drag-Pressure Flows in Extrusion) - Schöppner, Volker; Dörner, M.; Marschik, C.; Roland, W.; Schaufler, S.; Steinbichler, G. (Polymers)

CONTEXT OF FIBER LENGTH DISTRIBUTION, HOMOGENEITY AND MECHANICAL PROPERTIES IN DIRECT COMPOUNDING INJECTION MOLDING OF FIBER REINFORCED THERMOPLASTICS - Moritzer, Elmar; Wittke, M. (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

Development of a New Joining Technology for Hybrid Joints of Sheet Metal and Continuous Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Krassmann, Dimitri (73rd Annual Assembly of the International Institute of Welding (IIW))

Development of an Analytical Model to Describe the Disperse Melting in Wave-Dispersion Screws - Schöppner, Volker; Dörner, M.; Marschik, C.; Steinbichler, G. (Polymers)

Die Kunst der Entformung - Moritzer, Elmar; Jilg, J.; Schilp, C.; Krempl, N.; Friesenbichler, W. (Kunststoffe)

EINSATZ VON MASCHINELLEM LERNEN FÜR DIE REZYKLAT-VERARBEITUNG - Moritzer, Elmar; Hopp, Matthias; Wittke, Marius (WAK Jahreszeitschrift)

Entwicklung einer neuartigen Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Krassmann, Dimitri (Joining Plastics)

Entwicklung eines Spritzgießsonderverfahrens zur Herstellung von Hybridbauteilen aus faserverstärkten Thermoplasten und Metallblechen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (10. Fügetechnisches Gemeinschaftskolloquium)

INJECTION MOLD COOLED WITH ADDITIVE MANUFACTURED HEAT PIPE CORE-ELEMENT - Moritzer, Elmar; Kartelmeyer, S.; Hüttemann, M.; Jaroschek, C. (78th Annual Technical Conference for Plastics Professionals (ANTEC))

Inline Surface Activation in the multi Injection Molding Process - Moritzer, Elmar; Mühlhoff, Frederik Marvin (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

InMould-Plasma Technologie - Dauerhaft beständige 2K-Verbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Lochbaum, Ella; Krampe, Erhard (KGK - Rubberpoint)

An apparatus to synthesize ceramic nanoparticles with a precisely adjusted temperature history and a significant mass output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)

An Apparatus to Synthesize Ceramic Nanoparticles with a Precisely Adjusted Temperature History and a Significant Mass Output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)
For gas phase nanoparticle production, hot wall reactors are widely used. In this article, we will describe the fundamental design considerations for a hot wall reactor system able to produce oxide nanoparticles. The system is outstanding in its ability to produce mostly spherical nanoparticles at particle sizes of up to 100 nm and even larger at mass outputs in the order of grams per hour by being able to rapidly quench the aerosol. While high production rates or larger particle sizes are already easily obtained with hot wall reactors, it is very challenging to produce these spherical particles at high mass rates. We will show in this research that the temperature and the particle number concentration are the major aspects influencing the particle morphology at the end of the process. Investigation on the performance of the setup shows good control over the temperature and the particle production stability. A representative particle characterization using SEM and scanning mobility particle sizer showed that particles are mostly spherical, while the particle size distribution had a geometric standard deviation close to 1.5. In addition to the aspects mentioned above, a possibility to manipulate the aggregation downstream of the reactor is to be presented as well. We found that applying electrical charges to the aerosol particles (in opposite polarity) can significantly foster aggregation.

Investigation of Plastic Freeformed, Open-Pored Structures with Regard to Producibility, Reproducibility and Liquid Permeability - Moritzer, Elmar; Hirsch, André; Dalmer, C. (Additive Manufacturing in Products and Applications (AMPA))

Kostensenkung beim Mehrkomponenten-Spritzgießen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard (Kunststoff + Verarbeitung)

Mehr Materialkombinationen, weniger Kosten - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (Kunststoffe)

Metallsubstitution durch Spritzgießtechnik gerät allmählich in Reichweite - Moritzer, Elmar; Wittke, M. (MNWP Magazin)

More Material Combinations, Lower Costs - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (Kunststoffe international)

Neuartige Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Krassmann, Dimitri (DVS Congress 2020)

Neue Maßstäbe in puncto Festigkeit und Faserlänge - Moritzer, Elmar; Wittke, M. (Plastverarbeiter)

Plasma technology rationalizes 2-component processes - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhesion ADHESIVES + SEALANTS)

Plasma-Technologie zur Rationalisierung von 2K-Prozessen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhäsion KLEBEN & DICHTEN)

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Stainless steel parts produced by Fused Deposition Modeling and a sintering process compared to components manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, C. (4th International Conference Progress on Polymers and Composites Products and Manufacturing Technologies (POLCOM))

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Fiebig, Isabel; Schöppner, Volker (Joining Plastics)

Differences between the recycled carbon fibers especially regarding the product quality, - Malatyali, Hatice; Schöppner, Volker; Behrendt, Alexander; Hoemann, Theresa; Sporkmann, Frederick; Hanselle, Felix (SPE ANTEC)

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Schöppner, Volker (DVS CONGRESS 2020 - Große Schweißtechnische Tagung)

Vibration welding of components with angled areas in the direction of vibration - Vogtschmidt, Sascha; Schöppner, Volker (Welding in the World)

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

Antecedents and Performance Consequences of High-Potential Scheme Use - Krebs, Benjamin (Academy of Management Proceedings)

Kunststofftechnik Paderborn: Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen von Thermoplasten - Arndt, Theresa; Schöppner, Volker (Joining Plastics)

Wenn Regeln Potenziale freisetzen - Arndt, Theresa; Schöppner, Volker (K-Zeitung)

Quasi-Simultaneous Laser Transmission Welding - Arndt, Theresa; Schöppner, Volker (PhotonicsViews)

Modellierung des Wärmetransports in zyklisch durchströmten Wärmeübertragern - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppe „Energieverfahrenstechnik“)

Influence of Material Degradation on Weld Seam Quality in Hot Gas Welding of Polyamides - Schöppner, Volker; Bialaschik, Max (73th Annual Assembly of the International Institute of Welding (IIW))

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Interdiffusion in aluminum-steel clad strip - Krivská, Barbora; Šlapáková, Michaela; Kihoulou, Martin; Králík, Rostislav; Bajtošová, Lucia; Cieslar, Miroslav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Proc. 20th Conference of Czech and Slovak Physicists)

Device for twin-roll casting of strips with profiled cross-section - Bondarenko, Serhii; Grydin, Olexandr; Oginskiy, Yosyp; Kuzmina, Olga; Frolov, Yaroslav (Theory and practice of metallurgy)
Goal. This article is devoted to the development of a new method of roll-crystallizers profiling for twin-roll casting in order to provide the possibility of manufacturing strips with variable geometry on width as one of the more widely used products in the world. Method. The proposed method of profiling is implemented by using profiling strips that cover one or both rolls-crystallizers. In this way achieved profiling of the surface of the cylindrical internally water-cooled rolls, which corresponds to the desired type of strips profiled cross-section. Research results. For the practical implementation of the proposed profiling method was developed device for twin-roll of strips with profiled cross- section. In this paper presented the basic scheme of developed device for twin-roll casting of strips with profiled cross-section using endless strips and given the principle of operation of developed device for profiling. Scientific novelty. A feature of the developed device is its universality, which provides the possibility of synchronous rotation of tension, profiled and compensating-tension rollers in perpendicular plane to the axis of rotation of the rolls-crystallizers. This implementation of the device for twin-roll casting allows to manufacture different types of strips with profiled cross-section. Practical significance. For developed device for twin-roll casting of strips with profiled cross-section has been obtained patent for the invention of Ukraine. For further practical implementation of the developed device, considering the adjustments that provide practical implementation on a specific laboratory twin-roll casting unit, the device of twin-roll casting of strips with profiled cross-section was designed. In the work are presented the basic structural elements and their appearance in the form of three-dimensional models.

Aluminum-steel clad material prepared by twin-roll casting - KŘIVSKÁ, Barbora; ŠLAPÁKOVÁ, Michaela; Grydin, Olexandr; CIESLAR, Miroslav (METAL 2020 Conference Proeedings)

Deformation of expanded steel mesh inlay inside aluminum matrix during the roll bonding - Frolov, Yaroslav; Haranich, Yurii; Bobukh, Olexandr; Remez, Oleg; Voswinkel, Dietrich; Grydin, Olexandr (Journal of Manufacturing Processes)

Cold rolling of pre-profiled strips from aluminum alloy EN AW-1050 - Bondarenko, Serhii; Grydin, Olexandr; Frolov, Yaroslav; Kuzmina, Olga; Bobukh, Olexandr (Modern Problems of Metallurgy – Scientific Bulletin)

Large-scale heat pumps: Uptake and performance modelling of market-available devices - Jesper, Mateo; Schlosser, Florian; Pag, Felix; Walmsley, Timothy Gordon; Schmitt, Bastian; Vajen, Klaus (Renewable and Sustainable Energy Reviews)

Integration von Wärmepumpen zur Dekarbonisierung der industriellen Wärmeversorgung - Schlosser, Florian

Heat Pump Bridge Analysis Using the Modified Energy Transfer Diagram - Schlosser, Florian; Wiebe, Heinrich; Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R. W.; Hesselbach, Jens (Energies)
Heat pumps are the key technology to decarbonise thermal processes by upgrading industrial surplus heat using renewable electricity. Existing insight-based integration methods refer to the idealised Grand Composite Curve requiring the full exploitation of heat recovery potential but leave the question of how to deal with technical or economic limitations unanswered. In this work, a novel Heat Pump Bridge Analysis (HPBA) is introduced for practically targeting technical and economic heat pump potential by applying Coefficient of Performance curves into the Modified Energy Transfer Diagram (METD). Removing cross-Pinch violations and operating heat exchangers at minimum approach temperatures by combined application of Bridge Analysis increases the heat recovery rate and reduce the temperature lift to be pumped at the same time. The insight-based METD allows the individual matching of heat surpluses and deficits of individual streams with the capabilities and performance of different market-available heat pump concepts. For an illustrative example, the presented modifications based on HPBA increase the economically viable share of the technical heat pump potential from 61% to 79%.

Large-scale heat pumps: Applications, performance, economic feasibility and industrial integration - Schlosser, F.; Jesper, M.; Vogelsang, J.; Walmsley, T.G.; Arpagaus, C.; Hesselbach, J. (Renewable and Sustainable Energy Reviews)

Kombination und Integration etablierter Technologien mit additiven Fertigungsverfahren - Lieneke, Tobias; Künneke, Thomas; Eschner, Niclas; Jacob, Alexander; Schäfer, Martin; Hickmann, Thorsten; Faroun, Rami; Hoffmann, Markus; Scholl, Markus; Baumeister, Kai; Zimmer, Detmar; Lanza, Gisela

Efficient Cryptographic Constructions with Strong Security Guarantees - Kurek, Rafael

Transfer und Kooperation im regionalen Kontext. Erfahrungen aus der Forschung zu kommunalem Bildungsmanagement - Peter F. E. Sloane, Dieter Euler, Tobias Jenert (Berufsbildung in Wissenschaft und Praxis)

Neuartige Fügetechnik für Organoblech-Hybridverbindungen

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Pre-seasonal Assessment and Performance Diagnostics: Orthopaedic and Functional Aspects - Gokeler, Alli; Büchel, Daniel (Injury and Health Risk Management in Sports)

Peer Mentoring an der Fakultät für Wirtschaftswissenschaften - Konzept und Realisierungsformen - Sloane, Hannah; Kremer, H.-Hugo (Mentoring in Hochschuldidaktik und -praxis - Eine Reflexion wissenschaftlicher Erkenntnisse und praktischer Erfahrungen)

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

Experimental control of the degree of non-classicality via quantum coherence - Smirne, A; Nitsche, T; Egloff, D; Barkhofen, Sonja; De, S; Dhand, I; Silberhorn, Christine; Huelga, S F; Plenio, M B (Quantum Science and Technology)

Long‐term effects of hydrolyzed formulae on atopic diseases in the GINI study - Gappa, Monika; Filipiak‐Pittroff, Birgit; Libuda, Lars; Berg, Andrea; Koletzko, Sibylle; Bauer, Carl‐Peter; Heinrich, Joachim; Schikowski, Tamara; Berdel, Dietrich; Standl, Marie (Allergy)

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder - Libuda, Lars; Naaresh, Roaa; Ludwig, Christine; Laabs, Björn-Hergen; Antel, Jochen; Föcker, Manuel; Hebebrand, Johannes; Hinney, Anke; Peters, Triinu (European Journal of Nutrition)
Abstract Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide association study (GWAS) considering phenotype data from 79,366 individuals of European ancestry. Data on risk for ADHD were derived from a GWAS analysis with 20,183 individuals diagnosed with ADHD and 35,191 controls. For our analysis, we considered effect sizes based on the European participants (19,099 cases and 34,194 controls). Results Single SNP analyses showed a causal effect of vitamin D on ADHD risk for only one SNP (rs12785878, p = 0.024). The overall MR estimates did not reveal a causal effect of 25(OH)D on risk for ADHD. In the reverse analysis, neither any single nor the multi-SNP MR analyses showed a causal effect of ADHD on 25(OH)D. Conclusion Results from this two-sample MR study did not confirm a causal effect of 25(OH)D on ADHD or vice versa. Accordingly, our study does not provide evidence that improving 25(OH)D via supplementation could reduce the risk of developing ADHD.

The overall diet quality in childhood is prospectively associated with the timing of puberty - Duan, Ruonan; Qiao, Tian; Chen, Yue; Chen, Mengxue; Xue, Hongmei; Zhou, Xue; Yang, Mingzhe; Liu, Yan; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose The influences of nutrition in childhood on puberty onset could have sustained consequences for health and wellbeing later in life. The aim of this study was to investigate the prospective association of diet quality prior to puberty with the timing of puberty onset. Methods We considered data from 3983 SCCNG (Southwest China Childhood Nutrition and Growth) study participants with dietary data, anthropometric measurement, and information on potential confounders at their baseline assessment (mean age: 7.1 years for girls and 7.3 years for boys; mean length of follow-up was 4.2 years). Cox proportional hazard regression estimating hazard ratios (HRs) and 95% confidence intervals (CIs) were used to examine the relationship between diet quality and puberty onset. Dietary intake at baseline was assessed using a validated food frequency questionnaire. Diet quality was determined using the Chinese Children Dietary Index (CCDI) which measures adherence to current dietary recommendations (theoretical range: 0–160 points). Age at Tanner stage 2 for breast/genital development (B2/G2), menarche or voice break (M/VB) were used as pubertal markers. Results The CCDI score ranged from 56.2 to 136.3 for girls and 46.1–131.5 for boys. Pubertal markers consistently indicate that girls and boys with higher diet quality were more likely to enter their puberty later than their counterparts with lower CCDI scores (higher vs. lower CCDI tertiles: adjusted HR for age at B2: 0.85 (95% CI, 0.81–0.94), p for trend = 0.02; G2: 0.86 (95% CI,0.80–0.96), p for trend = 0.02; M: 0.86 (95% CI,0.80–0.95), p for trend = 0.02; VB: 0.86 (95% CI,0.79–0.98), p for trend = 0.03), after adjustment for paternal education level, baseline energy intake, and pre-pubertal body fat. Conclusions Our data suggested a later puberty onset and later timing of progressed puberty stages in children with a high diet quality, which were independent of pre-pubertal body fat.

Qualifizierung von Studierenden des Grund- und Förderschullehramts für den inklusiven Unterricht in der Grundschule - Franzen, Katja; Görel, Gamze; Hellmich, Frank; Filipiak, Agnes; Albers, Timm (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

School-based interventions to support student participation. A comparison of different programs. Results from the FRIEND-SHIP project - Hassani, Sepideh; Aroni, Katerina; Schwab, Susanne; Resch, Katharina; Toulia, Anastasia; Alves, Silvia; Görel, Gamze; Löper, Marwin Felix; Avramidis, Elias; Silveira- Maia, Mónica; Sanches-Ferreira, Manuela; Hellmich, Frank

Unterschiede in den Einstellungen zur Teamarbeit im inklusiven Unterricht zwischen Studierenden des Grund- und Förderschullehramts - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Expertiseentwicklung: Umwandlung von Wissen in Können - Harteis, Christian; Billett, Stephen; Gruber, Hans (Implizites Wissen. Berufs- und wirtschaftspädagogische Annäherungen)

Einstellungen von Kindern gegenüber Peers mit Förderbedarf: Die Rolle persönlicher Ressourcen für die soziale Partizipation. - Löper, Marwin Felix

Determinanten für die Einstellungen von Grundschulkindern gegenüber Peers mit einem sonderpädagogischen Förderbedarf in der emotionalen und sozialen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Die Ernährungsversorgung in Familien zwischen Zeit, Alltag und Haushaltsführung. Eine Mixed-Methods-Untersuchung - Klünder, Nina

Der Jugendamts-Monitor. Aufgaben – Trends – Daten - Müller, Heinz; Klünder, Nina

Optimal and Greedy Heuristic Approaches for Scheduling and Mapping of Hardware Tasks to Reconfigurable Computing Devices - Guetttatfi, Zakarya; Kaufmann, Paul; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Intrinsic Quality Assessment of Arguments - Wachsmuth, Henning; Werner, Till (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)